Culture and Content in French Frameworks for Innovative Curricula - Chevant-Aksoy, Aurélie; Adair Corbin, Kathryne (Lever Press, 2022)
Instructors in today's language classrooms face the challenge of preparing globally competent and socially responsible students with transcultural aptitude. As classroom content shifts toward communication, collaboration, and problem solving across cultural, racial, and linguistic boundaries, the teaching of culture is an integral part of foreign language education. This volume offers nontraditional approaches to teaching culture in a complex time when the internet and social networks have blurred geographical, social, and political borders.The authors offer practical advice about teaching culture with kinesthetics, music, improvisation, and communication technologies for different competency levels.The chapters also explore multi-literacies, project-based learning, and discussions on teaching culture through literature, media, and film.The appendices share examples of course syllabi, specific course activities, and extracurricular projects that explore culinary practices, performing arts, pop culture, geolocation, digital literacy, journalism, and civic literacy.